A unique role for ITK in survival of iNKT cells associated with the p53 dependent pathway in mice() - Qi, Qian (2012)
Invariant natural killer T (iNKT) cells play important roles in the immune response. ITK and TXK/RLK are Tec family kinases that are expressed in iNKT cells, with the expression level of ITK about 7-fold higher than that of TXK. Itk(−/−) mice have reduced iNKT cell frequency and numbers, with defects in development and cytokine secretion, which are exacerbated in the Itk/Txk DKO mice. By contrast, there is no iNKT cell defect in Txk(−/−) mice. To determine whether ITK and TXK play distinct roles in iNKT cell development and function, we examined mice that over express TXK in T cells to similar levels as Itk. Over expression of TXK rescues the maturation and cytokine secretion of Itk(−/−) iNKT cells, as well as altered expression of transcription factors T-bet, eomesodermin and PLZF. By contrast, the increased apoptosis observed in Itk(−/−) splenic iNKT cells is not affected by TXK over expression, likely due to lack of effect on the elevated expression of p53 regulated pro-apoptotic pathways Fas, Bax and Bad in those cells. Supporting this idea, p53(−/−) and Bax(−/−) mice have increased splenic iNKT cells. Our results suggest that TXK plays an overlapping role with ITK in iNKT cell development and function, but that ITK also has a unique function in the survival of iNKT cells, likely via a p53 dependent pathway.